Relationship between bone markers and cardiovascular risk factors in healthy Nigerian adults - Ale AO; Familoni OB; Ogunsemi OO; Afe TO; Adeleye OO; Adeyemo OL (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2020)
Background: Osteoporosis and cardiovascular diseases are global public health concerns. Both diseases have been linked through common risk factors and biological mechanisms. Objective: To evaluate the association between bone turnover markers (BTM) and some cardiovascular risk factors among healthy Nigerian adults. Methods: This was a cross-sectional, observational study of 80 healthy participants of less than 50 years of age. Clinical data were obtained through an interviewer-based questionnaire. Fasting blood samples were analysed for Osteocalcin (OC), Total Alkaline phosphatase (ALP), 25-hydroxyvitamin D (25-OHVitD), Calcium (Ca), Fasting Blood Glucose (FBG). Two-hour postprandial blood glucose (2HPP) Calcium-phosphorus product calculated (CAP) and 24-hour urinary calcium excretion (CaE) were determined. Results: The mean age of the participants was 32.1±5.8 years, mean BMI was 26.3±4.0kg/m2 and the mean waist circumference (WC) was 79.6±16.0cm. OC was directly correlated with ALP (r = 0.4, p = 0.006) but not with CaE (p = 0.8). Serum OC was inversely correlated with age, BMI and WC. ALP was negatively correlated with FBG (r = - 0.3, p = 0.04), 2HPP (r = - 0.65, p = 0.000). Multivariate regression showed that BTMs-OC, ALP and CAE independently predicted BMI, 2HPP, DBP and FBG respectively. Conclusion: This study showed a relationship between bone markers and selected cardiovascular risk factors in Nigerian adults. Therefore, patients with cardiovascular disease may benefit from bone health screening or vice versa.